Penerapan Model Pembelajaran M-APOS untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis - Rahmi Putri; Mukhaiyar Mukhaiyar; Azwar Ananda (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2022)
This study aims to determine the improvement of students' ability to understand mathematical concepts through the application of the Modification-, Action, Process, Object, and Schema (M-APOS) learning model. The type of research conducted is quantitative research with a quasi-experimental method. This research uses a research design of The Randomized Pre-test Post-test Control Group Design. The population in this study was all class VIII at MTsN 2 Kerinci in the 2018/2019 school year. Through random sampling, it was obtained that class VIII C as the control group to be taught conventionally and class VIII A as the experimental group to which M-APOS learning would be applied, these two classes consisted of 26 students. The results of this study indicate that the hypothesis test I proved that the Modification – action, process, object, and schema (M-APOS) learning model can improve students' ability to understand mathematical concepts in relation and function material for class VIII MTsN 2 Kerinci. While the results of the hypothesis test II obtained the ability to understand students' mathematical concepts with the application of the learning model (M-APOS) is better than the ability to understand students' mathematical concepts with conventional learning. Keywords: Concept Understanding Ability, Modification Learning Model – action, process, object, and schema (M-APOS), Experiment Class and Conventional Class